2015
DOI: 10.1177/1541931215591012
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Integrated Maneuver Guidance Information on UAS Pilots Performing the Detect and Avoid Task

Abstract: Nine active unmanned aircraft system (UAS) pilots were tasked with flying a simulated UAS in civil airspace and instructed to maintain safe separation (i.e., well clear) from surrounding traffic. Pilots' task of maintaining separation (referred to here as 'Detect-and-Avoid', or DAA) was facilitated by four different traffic displays, each differing in the level of maneuver guidance they presented to the pilot. Pilots were found to spend the least amount of time implementing a maneuver when provided with an int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
3
3
1

Relationship

3
4

Authors

Journals

citations
Cited by 18 publications
(7 citation statements)
references
References 6 publications
0
7
0
Order By: Relevance
“…It must be determined which conflict resolution tools make significant contributions to the observed benefits on performance and subjective assessments in the advanced display configuration. Rorie and Fern (2015) have since investigated the distinct impact of the vector planning tools and direct maneuver guidance found in the present study's advanced information condition. Further research is needed to identify the minimum DAA display requirements necessary for safe and efficient UAS operations in the NAS.…”
Section: Discussionmentioning
confidence: 99%
“…It must be determined which conflict resolution tools make significant contributions to the observed benefits on performance and subjective assessments in the advanced display configuration. Rorie and Fern (2015) have since investigated the distinct impact of the vector planning tools and direct maneuver guidance found in the present study's advanced information condition. Further research is needed to identify the minimum DAA display requirements necessary for safe and efficient UAS operations in the NAS.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, this simulation showed that UAS pilots benefited from advanced displays. Rorie and Fern (2015) examined three different types of advanced displays against a basic display (information only). The three advanced displays differed in terms of whether guidance for maintaining well-clear and/or collision avoidance provided to the pilot was in the form of a single maneuver (auto-resolutions), a "probing" tool (vector planner; allowed pilots to test whether specific headings or altitudes were conflict-free), or both (vector planner + auto resolutions).…”
Section: Should Advanced Information Elements Be Included? If So Howmentioning
confidence: 99%
“…Maintaining well-clear requires that UAS pilots are able to separate their aircraft from other traffic to maintain a safe distance. Because UAS pilots are operating the aircraft from a ground control station remotely and are not colocated with their aircraft (as with manned aircraft), the terms “sense-and-avoid” (e.g., Lee et al, 2013) or “detect-and-avoid” (e.g., Rorie & Fern, 2015) are often used instead of see-and-avoid. Moreover, in contrast to how pilots of manned aircraft maintain well-clear (i.e., through direct line-of-sight), UAS pilots must rely on surveillance and alerting systems that provide information on how close the UAS is to other aircraft so that pilots can maintain well-clear remotely (e.g., Lee et al, 2013; Santiago & Mueller, 2015).…”
mentioning
confidence: 99%
“…These limitations make ACAS II at best a temporary choice for UASs' collision avoidance. Various replacements have been proposed like JADEM (NASA) [16], MuSICA (AFRL) [17], MIDCAS (SESAR) [18] and ACAS Xu (FAA) [19]. Though no official successor has been chosen at the international level yet, ACAS Xu appears as a likely candidate.…”
Section: Limitationsmentioning
confidence: 99%